Application of Taguchi method to analyze the impacts of commonalities in multistage production under bottleneck and uncertainty - Wazed, M.A.; Ahmed, S.; Nukman, Y. (Academic Journals, 2010)
The work wishes to measure the individual and combined impacts of common parts and machines in manufacturing, under bottleneck and uncertain conditions. The system is characterized with multiple products, multi-period and multistage dependent demand. This research uses machine breakdown and quality variation to create uncertainty. The authors examined the delivery performances such as (i) throughput of the finished products, (ii) average production time and (iii) work-in-progress in the system for different experimental scenarios. Taguchi approaches for orthogonal array were employed in designing experiments and these were executed in a WITNESS. Few simulation models are developed based on a live case from a Malaysian company. The models corroborated and confirmed the historical data from the company by face validity. It was viewed that batch size of 12 in bottleneck, 2 common parts and 4 common machines ensure the best outcomes of the system under the storm of uncertainties. The main contribution of this research is to find out the best batch size in bottleneck point under uncertainties, commonalities and capacity constraint.